Analysis of Cooperation Between Furniture Industry and Designers in Product Development Process - Jordan Berginc (University of Zagreb, Faculty of Forestry and Wood Technology, 2011)
The aim of our research was to analyze the cooperation of furniture industry and designers in product development process. The results indicate the diffi culties of and impediments to such cooperation. SWOT analysis was used for analyzing the strengths and opportunities as well threats and weaknesses of cooperation of furniture industry with designers in product development process. The leading management of furniture companies and designers indentifi ed greater creativity (more innovative solutions), better design and more fresh ideas as the highest strength and opportunity of cooperation.